Developing Evidence to Decision Frameworks and an Interactive Evidence to Decision Tool for Making and Using Decisions and Recommendations in Health Care. Issue 9 (10th January 2018) - Rosenbaum, Sarah E.; Moberg, Jenny; Glenton, Claire; Schünemann, Holger J.; Lewin, Simon; Akl, Elie; Mustafa, Reem A.; Morelli, Angela; Vogel, Joshua P.; Alonso‐Coello, Pablo; Rada, Gabriel; Vásquez, Juan; et al.
Abstract: Evidence‐informed health care decisions and recommendations need to be made systematically and transparently. Mediating technology can help manage boundaries between groups making decisions and target audiences, enhancing salience, credibility, and legitimacy for all. This article describes the development of the Evidence to Decision (EtD) framework and an interactive tool to create and use frameworks (iEtD) to support communication in decision making. Methods : Using a human‐centered design approach, we created prototypes employing a broad range of methods to iteratively develop EtD framework content and iEtD tool functionality. Results : We developed tailored EtD frameworks for making evidence‐informed decisions and recommendations about clinical practice interventions, diagnostic and screening tests, coverage, and health system and public health options. The iEtD tool provides functionality for preparing frameworks, using them in group discussions, and publishing output for implementation or adaption. EtD and iEtD are intuitive and useful for producers and users of frameworks, and flexible for use across different types of topics, decisions, and organizations. They bring valued structure to panel discussions and transparency to published output. Conclusion : EtD and iEtD can resolve some of the challenges inherent in multicriteria, multistakeholder decision systems. They are freely available online for all to use athttps://ietd.epistemonikos.org/ andhttps://gradepro.org . Abstract : The purpose of Evidence to Decision frameworks is to help groups make systematic, transparent, and adaptable health care recommendations or decisions. This article describes the development of the frameworks and digital tool, revealing key stakeholder perspectives that are relevant for anyone seeking to use the framework, the tool, or develop similar approaches for decisions in other domains.